A Toolkit for the Management of Protocol Deviations. (November 2016) - Mohan, Sandy; Mehra, Munish; Petrizzo, Maryrose; Katz, Terry
Background: The DIA's Good Clinical Practice and Quality Assurance Community (DIA GCP/QA) created a working group to develop templates for a protocol deviation standard operating procedure (SOP) and protocol deviation handling plan (PDHP). Methods: The working group consisted of QA auditors, data managers, statisticians, and clinical monitors from several pharmaceutical companies, academia, and independent auditing firms. Various examples of standard operating procedures, data handling plans, and auditing plans were examined, and the core elements extracted into the initial PD SOP and PDHP templates. The draft templates were presented at a workshop at the DIA 51st Annual Meeting held in June 2015 in Washington, DC, and feedback was incorporated. The workshop came at the heels of a previously published position paper, "The Lifecycle and Management of Protocol Deviations." Results: The PD SOP and the PDHP templates are presented in this article. They are a starting point, and each company will need to modify to suit its individual needs. Conclusions: This article expands on the position paper to include concrete tools for the management of protocol deviations, including best practices for detection, classification, mitigation, and management of protocol deviations with a goal to reduce the impact on subject safety and data integrity.